Spatial Analysis of Flood and Landslide Vulnerable Areas (Case Study in Trenggalek Regency). (August 2019) - Riadi, B; Windiastuti, R; Suwarno, y
Abstract: Floods and landslides occurred almost every year in various regions in Indonesia, especially in hilly or bumpy areas. Floods and landslides as natural phenomena may cause severe disaster, due to high rainfall with small capacity of river cross section that resulted in water overflow through the dike and inundated lower areas. Flood and landslide risk mapping provides spatial information as initiation for mitigation purposes and is very beneficial in minimizing casualties and damages. To avoid landslide disaster, we need to reduce some causing factors, such as the factors that cause unstable slope conditions. The landslide distribution map contains information on geological maps, slope class maps, land cover maps and geomorphological maps; these maps are referred to as factor maps. Overlay method was implemented to analyse flood and landslide-prone areas. The purpose of this paper was to obtain information on areas in Trenggalek Regency that were vulnerable to flood and landslide. Risk analysis was done spatially with good accuracy, so that it can be used for disaster mitigation purposes.